Summary and Analysis of Practice Course Reader and their information needs - Chacón Rojas, Gilda (1983)
Practice on the education of the users realized in the following ones bibliotecas:Biblioteca of the College Maria Auxiliadora, Library of the College Go out For Her, Library of Heredia's Technical Professional College, Library of the Lyceum Manuel Benavides, Library of the Lyceum Samuel Sáenz.